Optimal residential load scheduling based on time varying pricing scheme - Haider H.T.; See O.H.; Elmenreich W. (Institute of Electrical and Electronics Engineers Inc., 2023)
Costs; Domestic appliances; Electric power transmission networks; Electric utilities; Energy utilization; Housing; Iterative methods; Sales; Scheduling; Demand response; Dynamic scheduling; Information and Communication Technologies; Iterative Optimization; Load scheduling; Smart grid; Time-of-use pricing; Utility companies; Smart power grids